Análisis, diseño, desarrollo e implementación de un sistema de georeferenciación de operadores económicos para la Superintendencia de Control del Poder de Mercado - Cáceres Díaz, Iván Fernando (2016)
La Superintendencia de Control del Poder de Mercado (SCPM) in their quest to incorporate new technologies, has developed a mobile application to determine the exact location of pharmacies, as a first stage those found in the city of Quito and this form verify they abide or fail to comply the law before the state. The web application management's main purpose to help manage information from pharmacies whether independent or chain. In addition economic operator’s pharmaceuticals may enter and update their information through this application. The chapters contained in this document are described below. In the first chapter is detailed the information corresponding to La Superintendencia de Control del Poder de Mercado, his objectives and reason to be. It also describes the different theoretical contents that have been investigated and are of interest for the development of web and mobile applications of the project. The second chapter refers to the requirements requested in the first instance by the client, which were reflected by a design methodology software development with his corresponding diagrams. In the third chapter the technologies and tools that have been used for coding and implementation of applications, which were subsequently tested for obtaining the performance and functionality, ending with the respective conclusions and recommendations of the work developed.